ROAD MAP AND DEVELOPMENT HALAL INDUSTRY SECTOR IN INDONESIA - Kadir, Syahruddin; Siradjuddin, Siradjuddin; Nur, Abustan; Efendy, Ahmad; Alaaraj, Hassan (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2024)
The purpose of this research is to find out the halal industry roadmap and the development of the halal industry sector in Indonesia. This research uses a literature review. The literature review uses data from trusted sources to be the research method of the technique used. The result of this study is that the halal industry in Indonesia began with research on food and beverage products found to contain pork extracts in 1988, so the government acted to form the MUI Food, Drug and Cosmetics Assessment Institute (LLPOM) officially in 1989 as the first halal inspection agency in Indonesia. The findings of this study suggest that stakeholders involved in the growth of the halal industry in Indonesia should support the halal industry roadmap. The halal industry business is developing in several sectors, including manufacturing, infrastructure, services, human resources, and halal certification standards. To overcome the demands of the growing halal industry in Indonesia, the government, business companies, and academics must collaborate and synergize to achieve the goal of making Indonesia a global halal center. The halal roadmap will help build and grow the halal ecosystem more methodically and comprehensively.